Gut Microbial Composition Is Associated with Symptom Self-Report in Trauma-Exposed Iraq and Afghanistan Veterans - Y. Irina Li; Kathleen Pagulayan; Holly Rau; Rebecca Hendrickson; Abigail G. Schindler (Neurotrauma Reports)
Iraq and Afghanistan War-era Veterans are at elevated risk for physical injuries and psychiatric illnesses, in particular the polytrauma triad of mild traumatic brain injury (mTBI), post-traumatic stress disorder (PTSD), and chronic pain. The gut microbiome has been implicated in modulation of critical processes beyond digestion, including immune system functioning and stress responsivity, and may be an important factor in understanding physical and mental health outcomes following deployment and trauma exposure. However, minimal research to date has sought to characterize gut microbiome composition in this population. Male Veterans of the conflicts in Iraq and Afghanistan who previously completed a Veterans Affairs’ comprehensive TBI evaluation were enrolled in the current study. Participants completed self-report measures of PTSD symptom severity, pain intensity and interference, fatigue, cognitive symptoms, substance use, and sleep quality. They also submitted fecal samples, and metagenomic sequencing was used to calculate alpha and beta diversity and taxonomic microbial composition. Associations between microbiome data and clinical variables were then examined. Alpha and beta diversity measures were not significantly correlated with clinical outcomes. Fatigue, post-concussive symptoms, executive function symptoms, and cannabis use were associated with differences in gut microbial composition, specifically Verrucomicrobiota. Together, results suggest that altered gut microbiome composition is associated with psychiatric and cognitive symptoms in Veterans and highlight a potential new therapeutic target of interest. Future research is needed to examine whether probiotic treatment is effective for reducing symptoms common in this clinical population.